RILPL2 as a potential biomarker for predicting enhanced T cell infiltration in non-small cell lung cancer - Dongfang Chen; Hongyan Zhang; Lifang Zhao; Xueqing Liu; Yueyan Lou; Peiling Wu; Shan Xue; Handong Jiang (Immunologic Research, 2024)
Our previous bioinformatics analysis has revealed that Rab-interacting lysosomal protein-like 2 (RILPL2) is associated with tumor immune microenvironment in non-small cell lung cancer (NSCLC). In our study, we collected 140 patients with primary NSCLC to verify the RILPL2 expression and its prognostic value, the relationship between RILPL2 expression and CD4 + , CD8 + T cell infiltration. A total of 140 patients who had been diagnosed with primary NSCLC (including 66 lung adenocarcinomas and 74 lung squamous cell carcinomas) were enrolled in our study. Immunohistochemical (IHC) staining was performed to analyze the expression of RILPL2, CD4, and CD8 in these patients. Compared with peri-cancer tissues, the RILPL2 expression in NSCLC tissues was significantly lower ( P < 0.0001). RILPL2 expression was significantly related to clinical stage ( P = 0.019), and low RILPL2 expression indicated higher stage. Low RILPL2 expression predicted worse overall survival (OS) in NSCLC patients ( P = 0.017). Correlational analyses revealed that RILPL2 expression was significantly positively correlated with CD4 + T cell infiltration in NSCLC ( R = 0.294, P < 0.001), LUAD subgroup ( R = 0.256, P = 0.038), and LUSC subgroup ( R = 0.333, P = 0.004); RILPL2 expression was also significantly positively correlated with CD8 + T cell infiltration in NSCLC ( R = 0.263, P = 0.002), LUAD subgroup ( R = 0.280, P = 0.023), and LUSC subgroup ( R = 0.250, P = 0.031). In conclusion, RILPL2 expression was downregulated in NSCLC; low RILPL2 expression was significantly related to higher stage and worse prognosis; RILPL2 expression was significantly positively correlated with CD4 + , CD8 + T cell infiltration.